PENGARUH MANFAAT, KEPERCAYAAN, DAN KEMUDAHAN PENGGUNAAN TERHADAP MINAT NASABAH MENGGUNAKAN LAYANAN MOBILE BANKING PADA PT. BANK PEMBANGUNAN DAERAH SUMATERA BARAT CABANG KOTO BARU, DHARMASRAYA - Jhon Fernos; Mairizal Alfadino (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2021)
This research aims to test the effect of benefits, trust, and ease of use on customer interests using mobile banking services at PT. West Sumatra Regional Development Bank Koto Baru Branch, Dharmasraya. The variables used in this study are bound variables i.e. customer interest (Y), and free variables consist of benefits (X1), trust (X2), and ease of use (X3). The type of data used in this study is quantitative data. The accumulation of data used in this study was primary data from questionnaires and using teknik slovin. Technical data analysis using classic assumption test, multiple linear regression analysis, and t test. The population in this study was a customer of PT Bank Pembangunan Daerah Sumatera Barat Koto Baru Dharmasraya Branch, the sample in this study amounted to 148 respondents.The research data was collected from respondents' results and analyzed with liniear regression and hypothesis test. The results showed that the variable benefits did not have a positive and significant effect on customer interest with a t-count value of (1,138<1.665) dan untuk variabel kepercayaan berpengaruh positif dan signifikan terhadap minat nasabah dengan nilai t-hitung sebesar (25.426>1,655), furthermore for ease of use positive and significant effect on customer interest with a t-count value of (2,810>1,655).